INSTITUTE OF AIR AND SPACE LAW AND MASS COMMUNICATIONS: HISTORY AND CONTEMPORARY STUDIES - Шинкарук, Василь Дмитрович (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2010)
The article highlights the stages of historical development of the Institute of Air and Space Law and mass communications of National Aviation University, illustrates peculiarities of preparing lawyers and specialists in the area of information activity for aviation.